Effectiveness of a preventative multi-component training program for prospective memory performance among healthy older adults - Farzin, Azin (2018)
Aging affects older adults’ physical and psychological well-being. One of the most significant age-related changes could be found in cognitive functions. Hence, to promote healthy aging and longevity among older adults, a global interest regarding treating agerelated cognitive declines emerged. Cognitive training seems to be more successful, compared with the pharmacological treatments, in improving cognitive functions among older adults. Cognitive training includes strategy- and process-based approaches. Both approaches showed some advantages and disadvantages individually. Therefore, the literature suggested to use a combination of these two approaches (i.e., multi-component approach) to benefit from their advantages and surpass their disadvantages. One of the cognitive functions which is affected by age is Prospective Memory (PM). PM is the memory for future intentions and is an essential part of everyday life, especially among older adults. It has significant impacts on levels of independence and well-being as significant elements of healthy aging and longevity. Nonetheless, only a few studies have focused on PM training and improving levels of independence and well-being among older adults and these studies showed inconsistent results. Past studies focused on clinical populations, did not have adequate training approaches and targets, lacked strong study designs, and they did not consider older adults’ individualized characteristics and needs. Moreover, PM is closely associated with several other cognitive functions as well (e.g., episodic and working memories). As such, these functions can be adequately targeted by multi-component cognitive training programs to promote healthy aging among older adults. Consequently, this study developed a tailor-made, multi-component PM training program for healthy older adults. The current study aimed to evaluate the efficacy of the intervention on the levels of independence, negative mood and anxiety among healthy older adults. In addition, the current study was planned as a randomized controlled trial (RCT) within participants’ crossover design. The sample consisted of 25 healthy older adults, aged between 55 and 75 years who are members of University of Third Age (U3A) Kuala Lumpur/Selangor, their family members or friends. The study included two conditions: treatment and control (waiting list). The intervention was conducted within a six-week period and lasted two hours per session. Implementation of intentions was used as the strategy-based approach, whereas the process-based approach used a computer game called “virtual week.” Two follow-ups were conducted one and three months post-intervention. The baseline measures included PM performance, independence, negative mood and anxiety measures. A significant increase in PM performance and the level of independence were found (e.g., PM: F (2, 11) = 58.15, p < 0.05, ɳ2 = 0.91; level of independence: F (1, 12) = 80.18, ɳ2 = 0.87, p < 0.05). Moreover, the results revealed a significant reduction in negative mood and anxiety levels (e.g., negative mood: F (4, 9) = 17.03, ɳ2 = 0.88, p < 0.05; anxiety: F (4, 9) = 44.43, ɳ2 = 0.95, p < 0.05). The training effects were also persistent after three months from the last intervention session.